Universities, Stakeholders and Social Mission: Building Cooperation Through Action Research - Ewa Bogacz-Wojtanowska; Piotr Jedynak; Sylwia Wrona; Anna Pluszyńska (Routledge, 2023)
Today's universities are confronted with questions about the increasing scale of corporatisation and commercialisation, as well as their decreasing activity in the field of the social mission, i.e., engagement in the real problems of ordinary people, local communities and society at large. As a remedy for this problem, this book proposes using action research as a means of shaping collaboration between universities and their stakeholders, taking into account related benefits, opportunities and challenges. In this context, we understand action research somewhat more broadly, as universities' conducting useful research that becomes a domain of their social mission. The core message of this volume is the development of a cooperation process in which the university leaves its ""ivory tower,"" builds relationships with its stakeholders and, as a result, engages more effectively in social life. In this book, readers will find an original perspective on action research, the application of which enables mutual benefits for universities and their stakeholders. It presents the authors' original model of cooperation based on the AR approach and concrete examples of successful cooperation between universities and their stakeholders. Step by step, it illustrates how to initiate cooperation, conduct useful scientific research and together with stakeholders bring about changes in social life. This book will be of value to university managers, academics, students of social, management and economic sciences, as well as managers and specialists employed in organisations from various sectors that may be interested in cooperation with universities.
Keywords: 370; action research; business; cooperation; management; organization; social life; social mission; society; stakeholders; universities